2015
DOI: 10.1128/jb.00638-15
|View full text |Cite
|
Sign up to set email alerts
|

A λ Cro-Like Repressor Is Essential for the Induction of Conjugative Transfer of SXT/R391 Elements in Response to DNA Damage

Abstract: Integrative and conjugative elements (ICEs) of the SXT/R391 family are the main contributors to acquired multidrug resistance in the seventh pandemic lineage of Vibrio cholerae, the etiological agent of the diarrheal disease cholera. Conjugative transfer of SXT/R391 ICEs is triggered by antibiotics and agents promoting DNA damage through RecA-dependent autoproteolysis of SetR, an ICE-encoded CI-like repressor. Here, we describe the role of CroS, a distant Cro homolog, as a key component contributing to the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…1, blue arrows; Table 1). It also contained a regulatory region (eex, setCD, croS and setR), which can be activated upon DNA damage (Beaber et al, 2002;Garriss et al, 2013;Poulin-Laprade & Burrus, 2015) and a recombination system (bet/exo) responsible for generating hybrid forms . Moreover, sequence analysis of the entry exclusion gene, eex, confirmed that ICESh95 belongs to ICE exclusion group S (99 % nucleotide identity to eexS from ICE SXT MO10 ) (Marrero & Waldor, 2007).…”
Section: Genome Analysis Of the Clinical Strain Shewanella Sp Sh95mentioning
confidence: 99%
“…1, blue arrows; Table 1). It also contained a regulatory region (eex, setCD, croS and setR), which can be activated upon DNA damage (Beaber et al, 2002;Garriss et al, 2013;Poulin-Laprade & Burrus, 2015) and a recombination system (bet/exo) responsible for generating hybrid forms . Moreover, sequence analysis of the entry exclusion gene, eex, confirmed that ICESh95 belongs to ICE exclusion group S (99 % nucleotide identity to eexS from ICE SXT MO10 ) (Marrero & Waldor, 2007).…”
Section: Genome Analysis Of the Clinical Strain Shewanella Sp Sh95mentioning
confidence: 99%
“…Moreover, G+C content was 44.8, 47.2, and 46.9% for ICE Mfu Ind1a, ICE Mfu Ind1b, and ICE Mpr Chn1, respectively. Most of the core genes of SXT/R391 ICEs (Beaber et al, 2002; Wozniak et al, 2009; Spagnoletti et al, 2014; Carraro et al, 2015; Poulin-Laprade and Burrus, 2015; Poulin-Laprade et al, 2015) were found to be preserved and were arranged in the same syntenic order in the three elements (Figure 1A, Supplementary Table 1) and showed 60–99% sequence identity at the level of amino acid to the corresponding proteins encoded by SXT/R391 ICEs (Supplementary Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…All the SXT/R391 ICEs are chromosomal MGEs sharing a conserved integrase that mediates site-specific integration into the 5′ end of prfC or t-RNA-ser in the absence of a prfC site (Hochhut and Waldor, 1999; Hochhut et al, 2001; Burrus and Waldor, 2003; Burrus et al, 2006; Taviani et al, 2012; Carraro and Burrus, 2014; Luo et al, 2016). Members of this ICE family contain 52 conserved core genes, many of which are involved in integration/excision, conjugative transfer and regulation of the ICEs (Beaber et al, 2002; Burrus et al, 2006; Wozniak et al, 2009; Bi et al, 2012; Spagnoletti et al, 2014; Carraro et al, 2015; Poulin-Laprade and Burrus, 2015; Poulin-Laprade et al, 2015). In addition, five hotspots (HS1—5) and five variable (VRI—V) regions have also been identified (Lei et al, 2016), which contain variable genes conferring element-specific properties and providing beneficial phenotypes to their hosts (Osorio et al, 2008; Wozniak et al, 2009; Rodríguez-Blanco et al, 2012; Balado et al, 2013; Poulin-Laprade et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…That switch entails essentially a balance of the counteracting transcription factors CI, CII and Cro [46,47]. Interestingly, other ICEs of the SXT/R391 family carry this typical double negative feedback loop architecture, which may therefore control their (bistable) activation [20,22,32].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of its genetic makeup, ICE clc is very distinct from the well-known SXT/R391 family of ICEs and from ICE St1 /ICE St3 of Streptococcus thermophilus [11,20,21]. These carry analogous genetic regulatory circuitry to the lambda prophage, which is characterized by a typical double-negative feedback control [2022]. Transcriptomic studies indicated that about half of the ICE clc coding capacity (~50 kb) is higher expressed in stationary phase cultures grown on 3-chlorobenzoate (3-CBA), and organized in at least half a dozen transcriptional units [23].…”
Section: Introductionmentioning
confidence: 99%